ESTIMATION DE LA BIOMASSE AERIENNE DES FORETS DE TRANSITION DE LA RESERVE FORESTIERE DE YOKO, RD CONGO : Importance de l’allométrie hauteur-diamètre - Thierry, BENGWELA MONGOLU; Faustin , BOYEMBA BOSELA (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Evaluate the above-ground biomass stocks in the forests of the central basin Congolese is a priority in the context of the implementation of the policy of mitigation of climate change and the mechanism. To this end it is essential to have equations allometric estimating biomass stocks contained in the rainforests. The objective of this study is to study the relationship of allometric between height and diameter of the trees of the forests of transition of the forest of Yoko reserve and its implications for estimates of the aerial biomass across the plot permanent monitoring of the forest dynamics of the South block.Data 2237 trees of floristic inventory in 5 ha on 9 ha of this plot were used to determine the structural parameters and pull the first five important species by the calculation of the value index importance of species.The results showed that the allometry of height-diameter differs between species and the inclusion of the total height in the equations allometric for estimating ground biomass compared to the only use of the diameter, allows to significantly improve accuracy.